STUDIES ON VICKERS HARDNESS AND THE ELASTICITY MODULUS OF MATERIALS FOR DENTAL RESTORATION - Cristina Angela Ghiorghe; Claudiu Topoliceanu; Sorin Andrian; Vlad Cârlescu; Galina Pancu; Andra Claudia Gamen; Irina Nica; Gianina Iovan (Romanian Society of Oral Rehabilitation, 2018)
The aim of this study was to evaluate the Vickers hardness (HV), indentation and Young`s modulus to 4 materials of coronal restoration. Materials and methods Six samples of 5mm in diameter and 6 inches were made of the following materials: Filtek Z250 (3M ESPE Co.), Zmack Comp (Zermack SpA, Italy), Kalore (GC Corporation, Japan); Dyract eXtra (Dentsply De Trey Gmbh, Germany). After polymerization of the samples for 40 seconds using the LEDidition lamp (Ivoclaire Vivadent clinical, Austria), these were finished, polished and kept in distilled water at room temperature for 48 hours. The hardness was measured at the UMT-2 Tribometer (CETR), and the values obtained in GPA were converted to Vickers hardness (kgf/mm2). For each sample, six indentations were made and the mean of the values obtained was calculated. On the same device, the Young`s modulus was also measured for all samples. Results Statistical data showed that the mean HV and modulus of elasticity values were the folowing: Filtek Z 250> Zmack Comp> Dyract eXtra> Kalore. In the case of the depth of the indentation, the values were inversely proportional to the Vickers hardness of the materials: Kalore> Dyract eXtra> Zmack Comp> Filtek Z 250. Conclusion Vickers hardness and Young's modulus were higher to the microhybrid composite compared to nano-hybrid composite and compomer.